’n Teoretiese inleiding tot narratiewe hermeneutiek in die teologie - Yolanda Dreyer (HTS Teologiese Studies/Theological Studies, 2003)
A theoretical introduction to narrative hermeneutics in theology The premise of this article is that narrative hermeneutics as a method of research in theology departs from a dialectical relationship between hermeneutics and the method of interpretation. The article aims to describe and explain narrative as a “way of knowing”. It focuses on the form, content, function and context of myth. Myth is foundational to the lifestories of people and groups. The discussion on narrative theory applies Paul Ricoeur’s concept of the “hermeneutical arch” in narrative hermeneutics. The article concludes with the idea that narrative as a way of knowing is ideological critical and deconstructs dominant socio-cultural narratives. The story of Jesus of Nazareth as the foundational myth of the Christian faith community can function as a contra narrative in order to give meaning to people’s lives in the presence of God in a postmodern world.